2020
DOI: 10.25288/tjb.562552
|View full text |Cite
|
Sign up to set email alerts
|

Büyük Menderes Granbeni'nin Rolling Hinge (Yuvarlanan Reze) Modelinde Supra-Detachment (Sıyrılma Üstü) Havzadan Rift Havzasına Evrimi

Abstract: Batı Anadolu genişlemeli tektonik sistemi içinde Miyosen-Kuvaterner zaman aralığında iki tip havza gelişimi gözlenmektedir. Bunlar rolling-hinge (yuvarlanan reze) modelinde gelişen supra-detachment (sıyrılma üstü) ve rift havzaları olarak tanımlanmışlardır. Bu çalışmada Büyük Menderes Grabeni kuzey kenarı üzerindeki Buharkent-Buldan arasındaki bölgede yuvarlanan reze modelinin varlığına dair stratigrafik ve yapısal veriler ilk kez sunulacak ve bu verilere göre grabenin jeolojik evrimi tartışılacaktır. Elde edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 106 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…The Başçayır Formation is much thinner in one of the injection wells, Incirliova Enjeksiyon-4, and this could be accounted for by both faulting and synextensional sedimentation. The synextensional sedimentation interpreted from the varying thicknesses of sedimentary rocks from this model is consistent with observations from rock outcrops and interpretations of structural data in the BMG from other studies (Sümer et al, 2020).…”
Section: Implications For Sedimentation and Tectonicssupporting
confidence: 88%
See 1 more Smart Citation
“…The Başçayır Formation is much thinner in one of the injection wells, Incirliova Enjeksiyon-4, and this could be accounted for by both faulting and synextensional sedimentation. The synextensional sedimentation interpreted from the varying thicknesses of sedimentary rocks from this model is consistent with observations from rock outcrops and interpretations of structural data in the BMG from other studies (Sümer et al, 2020).…”
Section: Implications For Sedimentation and Tectonicssupporting
confidence: 88%
“…Based on gravity modeling, Alemdar (2015) and Mahatsente et al (2017) have suggested that the asthenospheric material has risen through the lithosphere up to the mantlecrust interface beneath the BMG at 29°E (Figure 5). Recent studies have suggested that the BMG evolved from a supra-detachment basin in the Miocene to a rift basin in the Pliocene and Quaternary using a rollinghinge model for basin evolution (Sümer et al, 2020).…”
Section: Tectonic Evolutionmentioning
confidence: 99%